Improving Speaking Performance in Early Secondary EFL Learners at SMPN 7 Palu - Silva Iriannur; Abd. Kamaruddin; Fadhilah Zamzam; Mochtar Marhum (MASI Mandiri Edukasi, 2026)
Speaking ability remains a challenge for many Grade Seven EFL students, particularly in terms of fluency and comprehensibility, which are essential components of effective oral communication. This study aims to investigate whether implementing structured group discussion can improve students’ speaking fluency and comprehensibility at SMPN 7 Palu. A quasi-experimental research design was employed, involving an experimental class that received five sessions of group discussion treatment and a control class that was taught through conventional instruction. Both groups were administered pre-tests and post-tests focusing on fluency and comprehensibility. The data were analyzed using paired-samples t-test procedures. The results indicate that students in the experimental class demonstrated significantly greater improvement in speaking performance than those in the control class. The findings were further supported by observational data indicating increased student participation, reduced hesitation, and clearer organization of ideas during speaking activities. These results suggest that structured group discussion provides an effective interactive learning environment that supports smoother speech and improved comprehensibility. Therefore, the regular use of group discussion is recommended as an instructional strategy to enhance junior high school students’ oral communicative competence.